2015
DOI: 10.1371/journal.pone.0128381
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Epitope in the N-Terminal Domain of CCR5 and Its Interaction with Antibody

Abstract: The CCR5 receptor plays a role in several key physiological and pathological processes and is an important therapeutic target. Inhibition of the CCR5 axis by passive or active immunisation offers one very selective strategy for intervention. In this study we define a new linear epitope within the extracellular domain of CCR5 recognised by two independently produced monoclonal antibodies. A short peptide encoding the linear epitope can induce antibodies which recognise the intact receptor when administered coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The cell membrane is represented with a green rectangle. Ribbon representation of CCR5 and 5p7-CCL5 three-dimensional structures were generated using PyMOL from PDB entry 5UIW ( 10 ), MVC from PDB entry 4MBS ( 11 ), and the FAB fragment of RoAb13 from PDB entry 4S2S ( 12 ).…”
Section: Is Ccr5 a Discardable Troublesome Receptor?mentioning
confidence: 99%
“…The cell membrane is represented with a green rectangle. Ribbon representation of CCR5 and 5p7-CCL5 three-dimensional structures were generated using PyMOL from PDB entry 5UIW ( 10 ), MVC from PDB entry 4MBS ( 11 ), and the FAB fragment of RoAb13 from PDB entry 4S2S ( 12 ).…”
Section: Is Ccr5 a Discardable Troublesome Receptor?mentioning
confidence: 99%
“…Indeed, it has previously demonstrated that immunization with ECL1 domain, in a linear conformation, does not elicit serological Abs responses that bind to the native molecule ( 111 ) and, moreover, in macaques, the immunization with ECL2 in its native conformation induces immune responses with expected properties ( 84 ). Nevertheless, Chain and colleagues have recently defined a new linear epitope of CCR5 within the N-terminus domain recognized by two independently produced mAbs; in particular, they found that RoAb13 Ab is capable to bind to both linear peptide and native form of the epitope and the sulfation of tyrosines at CCR5 N-terminus enhanced its binding to the peptide ( 119 ). RoAb13 has been previously reported to block HIV infection ( 120 ) but also blocks migration of monocytes after the chemokine binding to CCR5 or in the presence of inflammatory macrophage conditioned medium ( 119 ).…”
Section: Induction Of Anti-ccr5 Abs As Vaccination Strategymentioning
confidence: 99%
“…Nevertheless, Chain and colleagues have recently defined a new linear epitope of CCR5 within the N-terminus domain recognized by two independently produced mAbs; in particular, they found that RoAb13 Ab is capable to bind to both linear peptide and native form of the epitope and the sulfation of tyrosines at CCR5 N-terminus enhanced its binding to the peptide ( 119 ). RoAb13 has been previously reported to block HIV infection ( 120 ) but also blocks migration of monocytes after the chemokine binding to CCR5 or in the presence of inflammatory macrophage conditioned medium ( 119 ).…”
Section: Induction Of Anti-ccr5 Abs As Vaccination Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Four are often used as standards or models for crystallization studies 27 ; they are thaumatin, trypsin, lysozyme and catalase. The fifth was a target protein, antibody RoAb13, the structure of which was recently solved 28 . The ability of each CNM to induce nucleation was assessed by the presence of crystals in the metastable drops.…”
mentioning
confidence: 99%